2017
DOI: 10.1007/s11356-017-9742-6
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil mill effluent treatment and CO2 sequestration by using microalgae—sustainable strategies for environmental protection

Abstract: In this era of globalization, various products and technologies are being developed by the industries. While resources and energy are utilized from processes, wastes are being excreted through water streams, air, and ground. Without realizing it, environmental pollutions increase as the country develops. Effective technology is desired to create green factories that are able to overcome these issues. Wastewater is classified as the water coming from domestic or industrial sources. Wastewater treatment includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 146 publications
0
9
0
1
Order By: Relevance
“…The combination of an anaerobic-aerobic treatment approach integrates the benefits of both processes and thus ensures adequate bio-decomposition, a higher rate of degradations, more biogas/bio-fertilizer recovery, efficient nitrification and denitrification processes [37,147,148]. Essentially, at acclimatized state, the anaerobic bacteria significantly reduced the pollutants such as COD, BOD and TSS [149], while the aerobic treatment is much suitable for the removal of toxic gases such as ammonia [8,150,151]. In addition, at the aerobic treatment, further deterioration of the remnants COD and BOD is possible to obtain better permeates [38].…”
Section: Treatments Process Using Mbrmentioning
confidence: 99%
“…The combination of an anaerobic-aerobic treatment approach integrates the benefits of both processes and thus ensures adequate bio-decomposition, a higher rate of degradations, more biogas/bio-fertilizer recovery, efficient nitrification and denitrification processes [37,147,148]. Essentially, at acclimatized state, the anaerobic bacteria significantly reduced the pollutants such as COD, BOD and TSS [149], while the aerobic treatment is much suitable for the removal of toxic gases such as ammonia [8,150,151]. In addition, at the aerobic treatment, further deterioration of the remnants COD and BOD is possible to obtain better permeates [38].…”
Section: Treatments Process Using Mbrmentioning
confidence: 99%
“…However, traditional wastewater management systems exhibited several limitations, including larger area obligation, rigorous power requirement, as well as extensive maintenance, which increases the overall costs of the wastewater treatment process [31]. Therefore, alternative wastewater treatment process needs to be explored for efficient resource recovery from wastewater [32]. Therefore, the microalgae-based wastewater treatment process is considered more effective as well as having the potential for atmospheric CO 2 .…”
Section: Wastewater Treatment Processesmentioning
confidence: 99%
“…Several studies demonstrated the potential of microalgae-based wastewater treatment [28,30,31,35], and integrated biorefinery approaches have been proposed for biofuel production [36]. Recently, various species of microalgae have been explored for a variety of wastewater treatment, including brewery wastewater [37], domestic wastewater [38], textile wastewater [39], pharmaceutical waste streams [40], slaughter-house industry [41], heavy metal-containing wastewater [42], palm oil mill effluents [32], starch-containing textile wastewater [43], and agro-industrial wastewater [44]. Although a microalgal cultivation system for wastewater treatment offers several advantages, different challenges are also associated, which need to be remitted as summarized in Table 1.…”
Section: Wastewater Treatment Processesmentioning
confidence: 99%
“…The 100% POME (25.5 ± 6.36 FAU) had more darkness of color followed by 25% POME (9 ± 0.05 FAU) and lastly 10% POME (2 ± 0.05 FAU). The dark color of POME limits and blocks the penetration of light through the bottles to the immobilized microalgal cells in the POME media (Ding et al 2016;Hariz and Takriff 2017). Therefore, the very high POME concentration and the absence of light hinders photosynthesis, causing death to the microalgal cells.…”
Section: Physical Examinationmentioning
confidence: 99%